1890
DOI: 10.1017/s0261340900007554
|View full text |Cite
|
Sign up to set email alerts
|

XI.—On an Inventory of the Vestry in Westminster Abbey, taken in 1388

Abstract: All documents which bear upon the history of Westminster Abbey must have a considerable interest for Englishmen. A church in which so many of the English kings since the Conquest have been crowned and anointed will always be venerable in the eyes of the more thoughtful portion of our countrymen, just as Aken and Rhemes must be honoured by Germans and Frenchmen. But, unlike Rhemes, Westminster is not an episcopal church. It became cathedral only for a moment, after its suppression as a monastery, in the reign o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1973
1973
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The mitre in Munich shows St Thomas on one side being attacked by three knights (this is a frequent depiction, although there were in fact four assailants), and St Stephen on the other (Fig. 5) 18 What appears to be the same frontal is also listed in the 1540 Inventory. It has been suggested that this may have been the frontal given by Henry is also represented on the Bologna cope (mentioned above) which is embroidered principally with scenes from the Life of Christ.…”
mentioning
confidence: 82%
“…The mitre in Munich shows St Thomas on one side being attacked by three knights (this is a frequent depiction, although there were in fact four assailants), and St Stephen on the other (Fig. 5) 18 What appears to be the same frontal is also listed in the 1540 Inventory. It has been suggested that this may have been the frontal given by Henry is also represented on the Bologna cope (mentioned above) which is embroidered principally with scenes from the Life of Christ.…”
mentioning
confidence: 82%